Menghadapi Tantangan Digital: Respon Akuntansi Manajemen Terhadap Disruptive Technology - Yudhistira, Prillinaya; Setyo Wibowo, Nugroho; Wijaya, Dwi Indriani Fidiastutik; Resya, Fachmi; Andriyanto, Dicky; Yuniar, Eka (Jurnal Ilmiah Inovasi, 2024)
Disruptive technology refers to digitization that offers a variety of new software and programs for Management accounting practices that are useful for assisting reporting, planning, controlling, and decision-making processes. Digital forms of disruptive technology include Big data, Cloud computing, Blockchain, and Artificial Intelligence (AI). All of which lead to automation, visibility and analysis in utilizing structured and unstructured data to support the company's decision-making process. The adoption of digital technologies in Management accounting in fact provides new benefits and challenges simultaneously. This study focuses on how Management accounting responds to disruptive technology and how the impact of disruptive technology on Management accounting practices. This study concludes that the existence of technology and rapid business development has led to the transformation of management accountants in the form of a significant shift in how management accountant view themselves (identity) and their roles in the organization.